Long-Term Evaluation of Geosynthetic Reinforcement of Flexible Pavements Constructed over Thick Organic Soil Deposits. Issue 1 (January 2014) - Greene, James; Nazef, Abdenour; Choubane, Bouzid; Horhota, David
Many regions throughout Florida have thick deposits of organic soil. Roadways built over these deposits often exhibit differential settlement, significant rut depths, and extensive cracks in a relatively short period of time. The Florida Department of Transportation constructed an experimental project on a realigned portion of State Road 15 on the southeastern shore of Lake Okeechobee in Palm Beach County to evaluate the effect of geosynthetic reinforcement on pavement performance. This roadway traverses farmlands with deep layers of organic material just beneath the surface and has a history of poor performance. The experimental project included four 500-ft sections with combinations of geogrids and geotextiles placed below the base and above the organic material. A fifth section of similar length was constructed with no geosynthetic reinforcement and served as a control. In addition to geosynthetic reinforcement, the alignment was surcharged before construction. The investigation showed that surcharging alone significantly improved the pavement performance compared with historical pavement condition and rehabilitation records. Geosynthetic reinforcement doubled the equivalent single-axle loads allowed on the unreinforced section. A rigid geogrid or woven geotextile placed below the base appeared to provide a slightly stiffer and better-performing pavement than a flexible geogrid. This paper documents the research program and provides details on the improvement resulting from surcharging and geosynthetic reinforcement.